2013
DOI: 10.1021/jp312836q
|View full text |Cite
|
Sign up to set email alerts
|

Organothiols Self-Assembled onto Gold: Evidence for Deprotonation of the Sulfur-Bound Hydrogen and Charge Transfer from Thiolate

Abstract: Organothiol (OT) adsorption onto gold nanoparticles (AuNPs) and gold powder was studied in 50% aqueous ethanol and in water. The OT solution rapidly acidifies upon addition of AuNPs or Au powder, and the number of protons released into the solution is proportional to the amount of OT adsorbed onto the gold surface. Theoretical calculations and normal Raman and surface-enhanced Raman spectroscopic (SERS) measurements show that the pK a of the OTs adsorbed onto AuNP can be more than 10 pK a units smaller than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
71
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(82 citation statements)
references
References 39 publications
8
71
2
1
Order By: Relevance
“…[2][3][4][5][6] Understanding the binding properties and structure of the Au-thiolate motifs, and the properties of the Au-S interface in general, is of importance for different research areas such as nanoelectronics and catalysis. 7,8 It has been demonstrated for example that the Au-S interface is quite flexible.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] Understanding the binding properties and structure of the Au-thiolate motifs, and the properties of the Au-S interface in general, is of importance for different research areas such as nanoelectronics and catalysis. 7,8 It has been demonstrated for example that the Au-S interface is quite flexible.…”
Section: Introductionmentioning
confidence: 99%
“…24−27 Mechanistic study revealed that the organothiol binding to AuNPs occurs by releasing the The Journal of Physical Chemistry C Article sulfur-bound hydrogen atoms as protons, thereby the organothiol is in thiolate form on AuNPs. 24 In contrast, organothiol interacting with AgNPs proceeds by converting the surface silver oxide and surface silver atom into silver thiolate salt. 25,26 The presence of a relatively thick layer of the silver thiolate salt on AgNPs (Figures 6 and S9 in the Supporting Information) exclude the possibility for the dithiols to cross-link two AgNP as monolayer dithiolate linker.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This can be especially true for organodithiol interactions with AuNPs and AgNPs. Unlike monothiols that bind to AuNPs as monothiolates by releasing its sulfur-bound hydrogen as proton, 27 organodithiol binding to NPs is much more complicated. It can bind as a monomer on the same NP in both monothiolate and dithiolate forms (Figure 1(A)), or as a dithiolate monomer bridging two AuNPs (Figure 1(B)).…”
Section: Introductionmentioning
confidence: 99%
“…27,[33][34][35][36] The goal of this current study is to determine the structure and compositions of the alkanedithiol (ADT, HS-(CH 2 ) n -SH) adsorbed onto AuNPs and AgNPs in water, using a combination of SERS, inductively-coupled were purchased within the past four months and they are used as received. The reagent purity are all 95% or above.…”
Section: Introductionmentioning
confidence: 99%